PENGARUH OPERATING LEVERAGE, ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) TERHADAP RETURN ON ASSET PADA PT. SEPATU BATA TBK. PERIODE 2011-2018: accounting & finance - Asep Suryana, SE., M.AK (Ekonomedia, 2018)
The use of fixed assets in a company will make the company bear fixed costs (operating leverage) every period. This operating leverage decision will affect the Return On Assets of a company. Where the Return On Assets of the company is used by investors to see the extent to which the company can generate profits from the assets they have. Based on this, the authors give the title of this study, namely: "the effect of operating leverage on return on assets at PT. Bata Shoes Tbk. period 2011-2018 ". The research aims to: (1) Know how operating leverage at PT. Sepatu Bata Tbk, (2) Knowing how to return on assets at PT. Sepatu Bata Tbk, (3) How is the influence of operating leverage on return on assets at PT. Sepatu Bata Tbk.The method used in this research is descriptive associative with the ex post facto approach. The data collection method used is documentation. And sampling uses quota sampling. The data source used is secondary data with the type of data used is quantitative data. The method of testing statistical data uses the T statistical test with a significance level of 0.05 using the SPSS 25.0 program for windows.The results showed that operating leverage has a significant negative effect on return on assets, with a value of -3.098 and a significance value of 0.004 and a correlation value of -0.492, which means the level of the relationship is quite influential. The coefficient of determination is 0.242, which means that the magnitude of the effect of operating leverage on return on assets is 24.2% and the remaining 75.8% is influenced by other factors outside this study.